The Role of Contextual Information in Classifying Spontaneous Social Laughter - Rychlowska, Magdalena; McKeown, Gary J.; Sneddon, Ian; Curran, William (Journal of nonverbal behavior, 2022)
Laughter is a ubiquitous and important social signal, but its nature is yet to be fully explored. One of the open empirical questions is about the role of context in the interpretation of laughter. Can laughs presented on their own convey specific feelings and social motives? How influential is social context when a person tries to understand the meaning of a laugh? Here we test the extent to which the classification of laughs produced in different situations is guided by knowing the context within which these laughs were produced. In the current study, stimuli were spontaneous laughs recorded in social situations engineered to elicit amusement, embarrassment, and schadenfreude. In a between-subjects design, participants classified these laughs being assigned to one of the four experimental conditions: audio only, audio-visual, side-by-side videos of two interactants, and side-by-side videos accompanied by a brief vignette. Participants’ task was to label each laugh as an instance of amusement, embarrassment, or schadenfreude laugh, or “other.” Laughs produced in situations inducing embarrassment were classified more accurately than laughs produced in other situations. Most importantly, eliminating information about the social settings in which laughs were produced decreased participants’ classification accuracy such that accuracy was no better than chance in the experimental conditions providing minimal contextual information. Our findings demonstrate the importance of context in the interpretation of laughter and highlight the complexity of experimental investigations of schadenfreude displays.